A New Framework for Evaluating the Potential for Drug Law to Produce Stigma: Insights from an Australian Study. Issue 4 (December 2017) - Seear, Kate; Lancaster, Kari; Ritter, Alison
Alcohol and other drug-related stigma is a growing concern. Many organizations have called for a reduction in such stigma through law reform, but there is little sense of how, precisely, this might be achieved. This paper reports on a new method to examine the relationship between stigma and the law and establish a framework that can guide and inform future law reform efforts.